Prominent regionalizations in Mexico: Considerations at the national level and for the state of Oaxaca (2023)
This study considers the prominent regionalizations in Mexico on the academic level and the national territorial planning. They were examined for the state of Oaxaca, along with other regionalizations of this federal entity. The objective was to highlight the importance and usefulness of regionalizations for the territorial planning of development from the concepts of homogeneous and functional regions. The applied methodology is centered on collecting bibliographic and documentary information, accompanied by the digital processing of cartographic information through geographic information systems software. The results showed that these provide information on the environment, economic activities, biodiversity conservation priorities, and urban and rural dynamics at the national level. Regarding Oaxaca, the economic regions of Bassols, the ecological regionalization of the Secretariat of Environment and Natural Resources (SERMANAT), the functional regionalization of the Secretariat for Agrarian, Land and Urban Development (SEDATU), the regionalization of the National Commission for the Knowledge and Use of Biodiversity (CONABIO), and the eight ethnic-folkloric regions of the state of Oaxaca were analyzed. It was found that the analyzed regionalizations are complementary and fundamental for economic development planning with a territorial focus.